(untitled) (Training and Practice : Journal of Educational Sciences, 2019)
In our research, we dealt with the opportunities of the experiential learning in the development of social competences with the involvement of pupils from a school of Pécs Street that mainly teaches Romany and disadvantaged children. At the beginning of the research, we surveyed the current status of social competences in selected classes with personal questionnaires and interviews with the class teacher. Based on this, we created the themes of our occupations, which we conducted in the two semesters. Social competence development practices focused on the following areas: trust, self-confidence; cooperation, conflict management; sensitization; creativity development. At the end of the research, the competence assessment was performed again. The most significant change has been found in the area of mixed, trust and cooperation-based practice.